Thermal hysteresis analysis of finned-heat-pipe-assisted latent heat thermal energy storage application for solar water heater system - Shahab Bazri; Irfan Anjum Badruddin; Abdullah Yousuf Usmani; Saleem Anwar Khan; Sarfaraz Kamangar; Mohammad Sajad Naghavi; Abdul Rahman Mallah; Ali H. Abdelrazek (Case Studies in Thermal Engineering, 2022)
This work numerically investigates the performance of an innovative compact-design solar water heater (SWH) using evacuated tube heat pipe solar collectors (ETHPSCs) coupled with a latent heat storage tank (LHS tank). This system is thought to be an unwritten fourth generation of solar water heaters known as heat-pipe-assisted thermal batteries. The basic and explicit hypothesis is to store energy than a bulk of hot water, which is the key distinction in compared to the prior classical sorts. Using three phase change materials (PCMs) for high and low solar intensity categories in the tropical region of South East Asia, a computational effort is conducted to model the system and the given temperature headed for the supply output hot water. This research is validated by two interrelated experimental and analytical investigations. According to the results of 12-h charging (melting) process, the maximum mean temperature of the PCMs belongs to PCM C, Rubitherm (RT70HC), which indicates 101 °C during the defined typical high daily solar radiation. This value implies 2.02% error in compared to the reference study. Referring to the solid-liquid interface parameter, the maximum liquefied thickness is also for PCM C with 76 mm thickness. However, reaching the complete melting is required by further studies.